An Error Analysis of Subject-Verb Agreement in GEC102 Students’ Sentences: Basis for a Learning Guides - Alim, Nor-Ain Hassan (Randwick International of Education and Linguistics Science Journal, 2025)
The study's objectives were to give a learning guide and assess the respondents' subject-verb mistakes in the sentences. The study specifically aimed to address the following questions: What is the age and sex profile of the respondents? Which of the respondents' sentences include subject-verb errors? And what kind of learning guide is needed? The frequency count and simple percentage were employed in the analysis of the collected data to identify subject-verb mistakes in the sentences and to ascertain the profiles of the respondents. Moreover, the study's respondents were MSU–Lanao National College of Arts and Trades BEED-1A and BSED-1A students enrolled in GEC102 (Purposive Communication) during the first semester of the 2025–2026 academic year. The findings unveil that the majority of the respondents made mistakes with the sentences: (1) He always go (goes) to church on Sunday, with 79.49% errors; (2) In the morning, Inez drink (drinks) two cups of coffee, with 61.54% errors; and (5) Min Ju and her brother does (do) not talk to each other, with 84.62% errors. The results also imply that they erred in the action verbs' singular and plural forms. It is recalled that an action verb is plural in its root form. Additionally, it becomes singular when -s or -es is added to the verb. On the other hand, few of the respondents made a mistake on sentence (8) "The police is (are) coming right now," with 28.21% errors. This may indicate that most of them were proficient in using the linking verbs. The findings showed that even if the majority of respondents made mistakes in just three (3) out of ten (10) sentences, it was still advised to give the respondents a learning guide.